Neutrino Physics and Astrophysics - Bellini, G. (IOS Press, 2014)
This book contains chapters based on 9 of the lectures delivered at the Enrico Fermi School of Physics "Neutrino Physics and Astrophysics", held from 25 of July to 5 August 2011. The event was organized by the Italian Physical Society (SIF) jointly with the International School of Astro-particle Physics (ISAPP), a network whose aim is to build up an astro-particle community of both astrophysicists and particle physicists. Included are chapters on Neutrino oscillation physics (B. Kayser); Double-beta decay (E. Fiorini); Light neutrinos in cosmology (S. Pastor); Neutrinos and the stars (G.G. Raffelt); High energy neutrinos and cosmic rays (G. Sigl); Methods and problems in low-energy neutrino experiments (G. Ranucci); Methods and problems in neutrino observatories (M. Ribordy); New technologies in neutrino physics (L. Oberauer); and Perspectives of underground physics (A. Bettini). These are a followed by a section on the results presented in the form of posters by the Ph.D. students attending the school. The book will be of interest not only to participants of the school, but also to other Ph.D. students and young physicists.